WORKPLACE HARASSMENT: STATE OF THE ART AND STUDY GAPS (Gestão & Regionalidade, 2018)
Due to the hazards arising from workplace harassment and its harmful consequences for the maintenance of the physical and psychological integrity of employees, attention should be given to the issue within the scope of social and organizational studies. A bibliometric study was carried out: we have selected articles published between 2001 and October 2016 in relevant Brazilian journals in the areas of Administration and Social and Work Psychology, in addition to those presented at the EnAnpad congress. This study aims to provide an overview of the theoretical construction of a subject of social relevance, thus guiding future research. Increasing debates and researches are necessary, so there is a need to strengthen the field of study, since organizations is where it occurs. Keywords: Psychological harassment; workplace; state of the art; bibliometry; research agenda.